2016
DOI: 10.1155/2016/2831594
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Alcohol Use among a Sample of Nigerian Semirural Community Dwellers in Nigeria

Abstract: Objective. To determine the prevalence and correlates of alcohol use among a sample of Nigerian semirural community dwellers in Nigeria. Methods. In a single arm nonrandomized intervention study, the assessment of baseline hazardous and harmful alcohol use and associated risk factors was conducted in two semirural local government areas of Oyo State, Nigeria, with the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). Participants included 1203 subjects 15 years and older, recruited between Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
39
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 9 publications
12
39
3
Order By: Relevance
“…Evidence from regional areas of Nigeria has suggested that the lifetime prevalence of alcohol use was 57.9% [57], while the overall prevalence of current alcohol use ranged from 15 to 24% [57–60]. In Nigeria, there are some policy initiatives (excise tax on beer, wine and spirits, the national legal minimum age for on/off-premise sales of alcoholic beverages and regulations on alcohol advertising) to limit alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from regional areas of Nigeria has suggested that the lifetime prevalence of alcohol use was 57.9% [57], while the overall prevalence of current alcohol use ranged from 15 to 24% [57–60]. In Nigeria, there are some policy initiatives (excise tax on beer, wine and spirits, the national legal minimum age for on/off-premise sales of alcoholic beverages and regulations on alcohol advertising) to limit alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…A previous similar study used only ASSIST without diagnosing AUDs. 20 Finally our study was able to identify a good number of participants who were either in danger of going further to develop alcohol use disorders and as such received brief intervention, and those with alcohol use disorders who thereafter were referred for either more intensive counselling or for more intensive treatment in a specialized treatment facility after the initial brief intervention. Considering the fact that most of these participants did not present primarily as a result of alcohol use problems, but for other medical or surgical problems, it will be appreciated that the alcohol problems are usually missed in routine medical services.…”
Section: Discussionmentioning
confidence: 92%
“…This contrasts with the more than two thirds of the current drinking population found to have moderate to severe risk in a previous study. 20 However, this is still very worrisome considering that as noted in that study alcohol is related with a risk of adverse health consequences such as alcohol dependence, cancers and injuries. The significance of this results from the fact that though patients may seek consultation for alcohol related physical illnesses, clinicians are less likely to detect and institute treatment for alcohol use disorders.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Related to this is are high rates of HIV/AIDS, smoking and alcohol abuse as well as poor healthcare infrastructure and public health educational strategies [30] [31] [32] [33] [34]. Related to these are high rates of alcohol and tobacco use as well as increasing use of amphetamines and cocaine [30].…”
Section: Discussionmentioning
confidence: 99%